Take Advantage of Wasteful Batang Hari Irrigation For Electricity Services Improvement - Bambang Istijono; Abdul Hakam (Chemical Engineering Diponegoro University, 2015)
This paper describes the Batang Hari Irrigation prospect to meet the electricity needs in its surrounding area in order to increase the electrical service for every level society. The use of Batang Hari irrigation is far from its capacity. Un-used water and infrastructures from Batang Hari irrigation can be used to generate hydro-electric. Based on the results of this study, it can be concluded that the Batang Hari Irrigation can be used to generate electricity power up to 1.6 MW. This hydro power service can increase the level of electric service in West Sumatra Province more than 1%